Functionalized Alkaline Lignin for Removal of Lead in Aqueous Solution - Deliana Dahnum; Egi Agustian; Eka Triwahyuni; Anis Kristiani; Roni Maryana; Yanni Sudiyani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Lignin, the second most abundant natural polymeric globally, is considered the source of the renewable aromatic compound. It serves as an alternative feedstock for the elaboration of chemicals and polymers. However, even until now, it is still primarily used as a low-value fuel for boilers. In the current research, alkaline lignin was modified and used as an adsorbent for removing lead (Pb) in an aqueous solution. The functionalized alkaline lignin (FAL) was prepared by a Mannich reaction with formaldehyde and dimethylamine, followed by esterification of carbon disulfide. The FAL was characterized using CHN elemental analysis, X-Ray Fluorescence (XRF), Scanning Electron Microscopy (SEM), and Fourier Transform Infrared (FT-IR) to observe the changes in composition, morphology, and chemical structure. The analysis revealed that alkaline lignin was successfully modified using amine and carbon disulfide. The adsorption study shows that the lead concentration reduced to 93.7% after 2 hours in contact with FAL. The FAL adsorption capacity could obtain 0.44 mmol/g of lead.